2019
DOI: 10.1111/febs.15146
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac regeneration and remodelling of the cardiomyocyte cytoarchitecture

Abstract: Adult mammals are unable to regenerate their hearts after cardiac injury, largely due to the incapacity of cardiomyocytes (CMs) to undergo cell division. However, mammalian embryonic and fetal CMs, similar to CMs from fish and amphibians during their entire life, exhibit robust replicative activity, which stops abruptly after birth and never significantly resumes. Converging evidence indicates that formation of the highly ordered and stable cytoarchitecture of mammalian mature CMs is coupled with loss of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 197 publications
(215 reference statements)
1
35
0
Order By: Relevance
“…However, Porrello et al 18 observed a transient regenerative potential of the neonatal murine heart induced by the dedifferentiation of cardiomyocytes. Moreover, cardiomyocyte remodeling, which includes the restructuring of the normally existing structures and rearrangement of the cytoskeleton, is vital for the normal function of heart 19 . A recently proposed hypothesis states that cardiomyocyte remodeling is closely related to dedifferentiation, which is characterized by a switch in the expression pattern of mature cardiomyocytes to a more immature state, enabling cardiomyocytes to survive under unfavorable conditions, enter the cell cycle to proliferate and recover their functions 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Porrello et al 18 observed a transient regenerative potential of the neonatal murine heart induced by the dedifferentiation of cardiomyocytes. Moreover, cardiomyocyte remodeling, which includes the restructuring of the normally existing structures and rearrangement of the cytoskeleton, is vital for the normal function of heart 19 . A recently proposed hypothesis states that cardiomyocyte remodeling is closely related to dedifferentiation, which is characterized by a switch in the expression pattern of mature cardiomyocytes to a more immature state, enabling cardiomyocytes to survive under unfavorable conditions, enter the cell cycle to proliferate and recover their functions 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, upon injury, CMs are replaced by fibrotic tissue, often with deleterious consequences. Recent advances in understanding the endogenous program(s) regulating the proliferation of cardiomyocytes at the molecular level [reviewed in Deshmukh et al (2019), Heallen et al (2019), Ali et al (2020)] hold great promise for the development of new approaches to heart regeneration based on cell cycle re-activation. Unfortunately, a full characterization of the developmental pathway(s) of the mammalian heart and specifically of CMs, is hindered by an intrinsic difficulty in understanding the exact timing and interchange of proliferation and differentiation events (Velayutham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, reduced mitochondrial gene expression and decreased oxidative phosphorylation activity have been recently observed in proliferating cardiomyocytes in regenerating heart models 37 . Additionally, sarcomere disassembly is a pre-requisite to cardiomyocyte proliferation in models of spontaneous cardiac regeneration, such as zebrafish and neonatal mice 5,7,30,[32][33][34] , and reduced sarcomere expression and organization in cardiomyocytes has been linked to increased ability to proliferate 30,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…During the early postnatal development, the cytoarchitectural structure of cardiomyocytes shifts from loose spatial organization to highly organized and more efficient sarcomere units 28,30 . To evaluate a potential impact of GR ablation on this physiological reorganization, we performed ultrastructure analysis by transmission electron microscopy of GR-cKO and control cardiomyocytes at birth and during the early postnatal development.…”
Section: Gr-cko Reduces the Post-natal Cardiomyocyte Metabolic And Samentioning
confidence: 99%
See 1 more Smart Citation